Soil-site characterization on crop productivity in Alfisols of Eastern Ghats of Tamil Nadu, India - SRINIVASAN, R.; HEGDE, RAJENDRA; THILAGAM, V. KASTHURI; KUMAR, S. NAVEEN (Journal of Soil and Water Conservation, 2022)
The effect of toposequence, crop cultivation, and soil conservation practices on runoff and soil loss was investigated in Alfisols of South-Eastern Ghats (SEG) of Tamil Nadu using large-scale soil mapping (1:10000 scale) information. Major landforms on peninsular granite gneiss are divided into hillside slope (P1), foothills (P2), upper pediment (P3), and lower pediment (P4). Major land uses are mango, ragi, pulses, groundnut, sorghum, little millet, and forest. A detailed soil survey was done undertaking a profile study in each landform. Soil samples were collected from different horizons of soil profiles and analyzed different soil properties. Soils were shallow (